Decentralization and Regional Autonomy: Impacts on Local Governance in Post-Reformasi Indonesia - Rania Faiz; Lilliana Hayes; Ana Clara Santos; Fahri Prakoso (Artes Libres Institutum, 2025)
The decentralization and regional autonomy reforms implemented after the 1998 Reformasi marked a significant shift in Indonesia’s political landscape, devolving power to local governments. This paper investigates the impacts of decentralization on local governance, focusing on the effectiveness of regional autonomy in promoting development and addressing local needs. It examines the strengths and weaknesses of local government institutions, the challenges of intergovernmental relations, and the extent to which decentralization has enhanced democratic participation at the grassroots level. Through case studies of various provinces and districts, the paper analyzes the role of local elites, political dynasties, and corruption in shaping the outcomes of decentralization. The contribution of this research lies in its critical assessment of regional autonomy as a tool for enhancing democratic governance, providing policy recommendations to improve local governance and strengthen democratic accountability in Indonesia.